Varactor diode‐based dual‐band frequency tunable multiple‐input multiple‐output antenna. Issue 2 (12th December 2020) - Smida, Amor; Iqbal, Amjad; Selmi, Marwa; Althuwayb, Ayman A.; Mallat, Nazih Khaddaj
Abstract: A microstrip feed line‐based continuous frequency‐tunable dual‐band multiple‐input multiple‐output (MIMO) antenna is proposed in this article. The proposed antenna comprises four hook‐shaped radiators placed orthogonally to one another. The overall dimensions of the antenna are 45 × 45 × 1.6 mm 3 (0.77 λ g × 0.77 λ g × 0.027 λ g [where λ g is the guided wavelength at the lower tunable resonant frequency]). The proposed antenna operates at dual‐band, while tunability in the resonant frequencies is achieved by connecting varactor diodes with the radiating patches. The lower resonant band of the antenna can be tuned from 2.45 to 2.83 GHz (with the isolation of more than 17 dB in the whole operating band) and the upper frequency band is tunable from 5.14 to 6.3 GHz (with the isolation of more than 22 dB in the whole operating band). The properties of the antenna such as reflection coefficients, mutual couplings, radiation patterns, channel capacity losses, and multiplexing efficiencies are verified by measuring the fabricated prototype. The envelope correlation coefficient of the antenna is < 0.11 for the lower frequency band and is < 0.16 for the higher frequency band for all tuning cases. The proposed antenna is suitable for use in compact multiband MIMO applications because of its small size, dual‐band characteristics, continuous frequency tuning capability, and good MIMO parameters.